2015
DOI: 10.1007/s11581-015-1376-4
|View full text |Cite
|
Sign up to set email alerts
|

High performance sulfur/nitrogen-doped graphene cathode for lithium/sulfur batteries

Abstract: A sulfur/nitrogen-doped graphene (S/N-G) composite was synthesized by simple sonicated mixing of nanosized sulfur suspension and nitrogen-doped graphene suspension followed by heat treatment. Scanning electron microscopy and energy dispersive spectroscopy mapping showed the formation of a porous structure with uniform distribution of sulfur and nitrogen-doped graphene. Electrochemical performance reveals that the resultant S/N-G composite exhibits a high reversible capacity of 1355 mAh g −1 at the initial cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Graphene can ideally trap S, restrict polysulfide dissolution and accommodate S volume change and hence, is of great interest for Li–S batteries . Cao et al synthesized FGS‐S multilayered 3D sandwich architectures with uniform S distribution on graphene surface.…”
Section: Li–s Batteriesmentioning
confidence: 99%
“…Graphene can ideally trap S, restrict polysulfide dissolution and accommodate S volume change and hence, is of great interest for Li–S batteries . Cao et al synthesized FGS‐S multilayered 3D sandwich architectures with uniform S distribution on graphene surface.…”
Section: Li–s Batteriesmentioning
confidence: 99%
“…Recently, Qin et al [ 22 , 23 , 24 ] reported that nitrogen doping of CNT could improve its surface activity and provide more nucleation sites to disperse metal oxide on its surface, which facilitates the morphology and particle size control of the hybrids. Specifically, nitrogen doping is considered as a feasible way to promote effectively the conductivity and reactivity of carbonaceous materials, which will increase electrochemical properties and reversible capacity of the hybrids, as has been experimentally and theoretically studied [ 25 , 26 , 27 ]. However, to our knowledge, only a few studies have been reported to date on synthesis and electrochemical properties of ZnO nanoparticles deposited on nitrogen-doped carbon nanotube (NCNT).…”
Section: Introductionmentioning
confidence: 99%
“…The design of multi-architectural and multi-functional cathode materials has the potential to overcome these challenges and has been one of the most researched strategies in recent years. Currently, physical routes including capillary force absorption [14,[51][52][53][54][55][56][57], shell coating [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75], and chemical routes containing heteroatom-doped carbons [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and metal-based additives [91][92][93][94][95][96][97][98][99]…”
Section: Fundamental Studies and Materials Selectionmentioning
confidence: 99%